2019
DOI: 10.1158/1078-0432.ccr-18-3663
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Detection of Circulating Tumor DNA Antedates Breast Cancer Metastatic Recurrence

Abstract: Purpose: Up to 30% of patients with breast cancer relapse after primary treatment. There are no sensitive and reliable tests to monitor these patients and detect distant metastases before overt recurrence. Here, we demonstrate the use of personalized circulating tumor DNA (ctDNA) profiling for detection of recurrence in breast cancer.Experimental Design: Forty-nine primary patients with breast cancer were recruited following surgery and adjuvant therapy. Plasma samples (n ¼ 208) were collected every 6 months f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
297
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 352 publications
(354 citation statements)
references
References 33 publications
8
297
0
9
Order By: Relevance
“…Numerous NGS technologies such as BEAMing and Safe-SeqS have been used to detect known breast cancer mutations using ctDNA with sensitivity higher than 99% 30 . Our own studies have shown for primary patients that recurred, patient specific ctDNA profiling detected molecular relapse up to 2 years ahead of clinical relapse with 89% sensitivity and 100% specificity 31 . However, despite its high sensitivity and specificity, NGS platforms are still costly and require specialist time for data analysis and experimentation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Numerous NGS technologies such as BEAMing and Safe-SeqS have been used to detect known breast cancer mutations using ctDNA with sensitivity higher than 99% 30 . Our own studies have shown for primary patients that recurred, patient specific ctDNA profiling detected molecular relapse up to 2 years ahead of clinical relapse with 89% sensitivity and 100% specificity 31 . However, despite its high sensitivity and specificity, NGS platforms are still costly and require specialist time for data analysis and experimentation.…”
Section: Discussionmentioning
confidence: 90%
“…DNA was extracted from a healthy control tissue core as a WT control (H1047R negative) and from a tumour patient core (H1047R heterozygous sample). Patient samples used in this study were from our recent paper Coombes et al 31 with the trial protocol approved by the Riverside Research Ethics Committee REC:13/ LO/115; IRAS:126462. Methods were carried out in accordance with the relevant guidelines and regulations.…”
Section: Methodsmentioning
confidence: 99%
“…26,27 Currently, the clinical utility of ctDNA is only approved in metastatic non-small-cell lung cancer (NSCLC) by FDA as a companion diagnostic, 28,29 while studies on many other cancers have also shown good prospects. [30][31][32][33][34][35][36] The fact that even little variability in process and analysis will result in completely different results restrains the further clinical utility of ctDNA. 37 In order to solve these problems, some projects, such as the European CANCER-ID, European Liquid Biopsy Academy (ELBA) and European Liquid Biopsy Society (ELBS) networks or the US-based BloodPAC, have been initiated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that liquid biopsies can detect minimal residual disease (MRD) in multiple cancer types (8)(9)(10)(11)(12) including breast (13)(14)(15), by tracking tumor mutations in circulating cell-free DNA (cfDNA). However, in these previous studies, clinical sensitivity has been limited at the early postoperative time points, at which treatment decisions are typically made, and the lead time prior to clinical presentation of overt metastatic disease has been relatively short.…”
Section: Introductionmentioning
confidence: 99%